Extended-spectrum β-lactamase (ESBL): Phenotypic detection and antimicrobial susceptibility pattern to ciprofloxacin, amikacin and imipenem (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Extended-spectrum β-lactamases (ESBLs) are enzymes capable of hydrolyzing extended-spectrum cephalosporins, penicillins and monobactams but inactive against cephamycins and carbapenems.Objectives: This study was aimed to detect ESBL by phenotypic confirmatory disc diffusion test (PCDDT) and to determine the susceptibility pattern of ESBL-producing E. coli,Klebsiella spp. and Enterobacter spp. to ciprofloxacin, amikacin and imipenem.Methods: A total of 100 ESBL-producing E. coli,Klebsiella spp. and Enterobacter spp. were obtained from Bangabandhu Sheikh Mujib Medical University, Dhaka and were studied for susceptibility pattern from October 2010 to December 2011. These isolates were identified by double disc synergy test (DDST) and were confirmed phenotypically as ESBL by PCDDT.Results: Out of 75 DDST positive ESBL-producing E. coli, 71 (94.67%) were also positive by PCDDT. All DDST positive ESBL-producing Klebsiella spp. and Enterobacter spp.  were also positive by PCDDT. All ESBL-producing E. coli,Klebsiella spp. and Enterobacter spp. were 100% susceptible to imipenem. About 95.78% ESBL-producing E. coli, 78.95% Klebsiella spp. and 100% Enterobacter spp. were susceptible to amikacin. About 87.32% ESBL-producing E. coli, 73.69% Klebsiella spp. and 33.33% Enterobacter spp. were resistant to ciprofloxacin.Conclusion: ESBL-producing E. coli, Klebsiellaspp. and Enterobacter spp. showed high resistance to ciprofloxacin. Imipenem and amikacin were most effective against ESBL-producing organismsJ.Dhaka National Med. Coll. Hos. 2015; 21 (01): 28-31